2018
DOI: 10.1667/rr14696.1
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Mitigates Radiation Injury in Human Umbilical Vein Endothelial Cells In Vitro via the Thrombomodulin Pathway

Abstract: Cell death and tissue injury occur as a result of radiation accidents and radiotherapy. The role of endothelial cell damage in mediating radiation-induced acute tissue injury has been extensively studied. We previously demonstrated that ferulic acid (FA) mitigates radiation-induced hematopoietic injury in mice and lessens radiation-induced oxidative damage in human umbilical vein endothelial cells (HUVECs). The purpose of the current study was to determine whether FA can protect HUVECs from radiation toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…26 Shao et al also found that ferulic acid can significantly improve the outcomes of HUVECs exposed to radiation by promoting cell viability and angiogenesis and arresting the G2/M cell cycle, which might be associated with decreased levels of HMGB1, IL-6, and IL8. 27 Besides, PRKX expression was also dependent on the amount of exposure, indicating a possible biological dosimeter.…”
Section: Discussionmentioning
confidence: 99%
“…26 Shao et al also found that ferulic acid can significantly improve the outcomes of HUVECs exposed to radiation by promoting cell viability and angiogenesis and arresting the G2/M cell cycle, which might be associated with decreased levels of HMGB1, IL-6, and IL8. 27 Besides, PRKX expression was also dependent on the amount of exposure, indicating a possible biological dosimeter.…”
Section: Discussionmentioning
confidence: 99%
“…142,143 Feeding black goji berry reduced p53 in intestinal crypt epithelial cells and decreased the caspase-3 and caspase-6 levels in the serum at the 3 rd , 7 th and 14 th -day post-irradiation assay time points 142,143 (Table 1). In addition to the extract, the phytochemicals naringin, [48][49][50][51][52][53] hesperetin, 62 luteolin, 86,87 quercetin, [23][24][25] chlorogenic acid 82,83 and ferulic acid [144][145][146][147][148] possess radioprotective effects (Table 2 and Fig. 1).…”
Section: Lycium Ruthenicummentioning
confidence: 99%
“…199 Subsequent studies have shown that the whole fruit extract effectively mitigates radiation-induced mucositis and dermatitis in head and neck cancer patients undergoing curative radiotherapy 200 (Table 1). The phytochemicals ferulic acid, [144][145][146][147][148] ellagic acid, 96,97 gallic acid 94,95 and chlorogenic acid 82,83 also possess radioprotective effects.…”
Section: Punica Granatum Lmentioning
confidence: 99%
“…Shao et al. ( 57 ) reported that ferulic acid (FA) can reduce the oxidative damage of radiation to endothelial cells. The thrombomodulin (THBD) pathway may be an important mechanism of FA against radiation injury.…”
Section: Intestinal Stem Cell Injurymentioning
confidence: 99%